MEMBANGUN BISNIS TANAMAN HIAS INDOOR DI KOTA KUPANG MELALUI KEGIATAN KEWIRAUSAHAAN MAHASISWA PROGRAM STUDI AGRIBISNIS FAKULTAS PERTANIAN UNIVERSITAS NUSA CENDANA - Agnes Wehelmina Alberthus; Marthen R. Pellokila; Nendissa, D. Roy; Chamdra, Santhy; Elvani, Siska (Jurnal Pengabdian pada Masyarakat Kepulauan Lahan Kering, 2024)
The indoor ornamental plant business in Kupang City is quite a promising business. The survey results provide an indication that the demand for indoor ornamental plants continues to grow. This provides a promising business opportunity if pursued professionally and strategically so that it can generate profits. The target market for this business is the people of Kupang City who need indoor ornamental plants, such as offices, lecture halls, residential houses, shady places, etc. The choice of types of indoor ornamental plants in this business are leaf ornamental plants and flower ornamental plants, with good quality provisions, regular maintenance and fertile, quality soil. The objectives of this activity are (1) Building students' entrepreneurial interest in the field of indoor ornamental plants; (2) Channeling your interest or hobby in ornamental plants; (3) Increase and popularize interest in ornamental plants among the people of Kupang City. The method used in this activity is direct student participation in the production and marketing process of indoor ornamental plants. As a result of this activity, the students involved were motivated to produce and pursue indoor ornamental plant business.